Network meta-analysis of the efficacy of four traditional Chinese physical exercise therapies on the prevention of falls in the elderly - Cheng, Meichao; Wang, Ya; Wang, Shun; Cao, Wenxiao; Wang, Xianliang (Frontiers in Public Health, 2023)
Introduction In recent years, traditional Chinese exercises have been passed down and reformed to play a significant role in the study of interventions for the treatment of falls in older people. However, few studies have evaluated the efficacy of various Chinese traditional exercises in the intervention of falls behavior in the elderly. In this study, four Chinese traditional exercises commonly used in clinical practice were selected as subjects to systematically evaluate the effectiveness of Tai Chi, Ba Duan Jin, Yi Jin Jing and Wu Qin Xi in intervening in the treatment of fall behavior in the elderly. Methods We conducted a systematic review in accordance with the PRISMA guidelines. Four published randomized controlled trials (RCTs) of traditional Chinese exercise interventions for the treatment of falls behavior in older adults were searched through authoritative databases such as CNKI, Web of Science, PubMed, EMbase and the Cochrane Library, all from the time of construction to November 2022. Results A total of 45 studies with 4 traditional interventions were included. Ba Duan Jin was more effective in improving TUGT [SMD = −1.93 (−2.49, −1.38), P < 0.05] and MFES [SMD = −33.45 (−63.93, −2.97), P < 0.05], while Yi Jin Jing was more effective in enhancing ECLSB [SMD = −0.19 (−5.12, −4.74), P < 0.05] and BBS [SMD = −5.79 (−10.80, −0.78), P < 0.05], both of which showed better effects. Discussion The present evidence suggests that all four traditional Chinese body-building exercise therapies have a preventive effect on fall behavior in older adults. In clinical treatment and daily physical exercise, two exercises, BaDuan Jin and Yi Jin Jing, may be preferred to reduce the risk of falls in the elderly, but the exercise regimen of Qigong should be selected scientifically and rationally according to their actual conditions. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/#myprospero.